Assessment of Esophageal Motility in Patients With Eosinophilic Esophagitis: A Scoping Review. Issue 1 (2nd January 2023) - Sykes, Catherine; Fairlamb, Grace; Fox, Mark; Sweis, Rami
Abstract : Eosinophilic esophagitis (EoE) is a chronic, immune-mediated condition causing esophageal symptoms, particularly dysphagia. Despite the important progress in the treatment of EoE, a significant proportion of patients continue to report symptoms that negatively impact quality of life. Esophageal manometry is used to assess motility and function, but is not routinely used in EoE. We aimed to systematically review and describe current literature evaluating esophageal manometry in EoE. Forty-eight studies meeting the criteria were identified, describing 802 patients. Using standard water swallow protocols, the proportion of abnormalities detected was not dissimilar to other populations, apart from disorders of esophago-gastric outflow, which were found in 5%. Twelve studies described pretreatment and posttreatment manometry, with motility normalization after pharmacological therapy reported in 20%. Early, brief panesophageal pressurization was described in a number of studies and was more prevalent in the few studies utilizing additional provocation testing. Reports in the literature regarding temporal relationships between manometric findings and symptoms are variable. Esophageal manometry may be capable of detecting clinically relevant changes to esophageal function in EoE. Possible mechanisms are altered neuromuscular function because of secretory products of EoE and/or fibroinflammatory processes, manifesting as pressurization because of altered esophageal compliance. Some changes may be reversible with therapy. Drawing strong conclusions from the literature is difficult, with bias toward case reports and retrospective observation. Adaptations to assessment protocols to include provocation testing may provide more robust evaluation and detect clinically relevant, subtle changes in esophageal function, earlier within the patient pathway.